Tadrij Ibn Khaldun dan Al-Sa'adah Al-Farabi: Landasan Pembelajaran Adaptif Berbasis Kecerdasan Buatan dalam PAI - Sita Acetylena; Saida Munawaroh (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
Artificial intelligence is entering Islamic Religious Education (PAI) classrooms, yet AI-based personalization risks collapsing into pure cognitive optimization without explicit philosophical grounding, while existing Islamic education literature responding to the AI era generally stops at general value statements without descending to technical specification or testing against established Western pedagogical theory. This study aims to formulate an integrative philosophical framework from Ibn Khaldun's principle of tadrij and Al-Farabi's thought on ta'dib, ta'lim, and al-sa'adah, map that framework onto the technical components of an AI-based adaptive learning system, and test it against Bloom's mastery learning, Vygotsky's zone of proximal development, and Aristotelian eudaimonia as comparative theories. The study applies a qualitative library research design, analyzing primary texts from the Muqaddimah and Al-Farabi's treatises alongside secondary and tertiary sources on AI-based adaptive learning, AI ethics in education, and Western pedagogical theory. Of the corpus reviewed, thirty-three sources were selected for primary analysis. Content analysis produces a three-stage conceptual mapping, from general introduction to consolidating repetition, corresponding to diagnostic assessment, dynamic sequencing, and mastery-check loops in AI systems, while showing that al-sa'adah fills a character-based normative criterion absent from both AI adaptive learning literature and its secular eudaimonic counterpart. The study concludes that the staging principle in classical Islamic education has a structural counterpart in modern AI architecture but offers a philosophically deeper success criterion than its Western counterpart, a contribution that opens space for character-oriented rather than merely performance-oriented PAI adaptive learning design. Keywords: Adaptive Learning, Al-Sa'adah, Artificial Intelligence, Islamic Religious Education, Tadrij